Managing Pests of Indoor Plantscapes - Eileen A. Buss; Lance S. Osborne; S. M. Dickerson; James F. Price (EDIS)
Revised! ENY-694, a 9-page fact sheet by E. A. Buss, L. S. Osborne, S. M. Dickerson, and J. F. Price, is part of the Florida Master Gardener Handbook. It describes special aspects of interiorscape pest management. Includes a diagnostic guide for plants grown indoors, products available for interiorscape pest management, and inset and mite pesticide options. Published by the UF Department of Entomology and Nematology, November 2007.